Synthesis, Optical Characterization, and Size Distribution Determination by Curve Resolution Methods of Water-Soluble CdSe Quantum Dots - Santos,Calink Indiara do Livramento (2016)
In this work a colloidal approach to synthesize water-soluble CdSe quantum dots (QDs) bearing a surface ligand, such as thioglycolic acid (TGA), 3-mercaptopropionic acid (MPA), glutathione (GSH), or thioglycerol (TGH) was applied. The synthesized material was characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR), UV-visible spectroscopy (UV-Vis), and fluorescence spectroscopy (PL). Additionally, a comparative study of the optical properties of different CdSe QDs was performed, demonstrating how the surface ligand affected crystal growth. The particles sizes were calculated from a polynomial function that correlates the particle size with the maximum fluorescence position. Curve resolution methods (EFA and MCR-ALS) were employed to decompose a series of fluorescence spectra to investigate the CdSe QDs size distribution and determine the number of fraction with different particle size. The results for the MPA-capped CdSe sample showed only two main fraction with different particle sizes with maximum emission at 642 and 686 nm. The calculated diameters from these maximum emission were, respectively, 2.74 and 3.05 nm.